a rememory that belongs to somebody else: Stories of (un)welcoming - Wane, Anna Karima (Taideyliopiston Kuvataideakatemia, 2024)
a rememory that belongs to somebody else is the graduation work of Anna Karima Wane at the Academy of Fine Arts, University of the Arts Helsinki. It consists of an exhibition which took place 4-12 May 2024 at the Museum of Impossible Forms in Helsinki, and a written thesis project. The exhibition centered around issues of archive and memory through the lens of the artist’s family histories. Wane explores the place their own family history occupies among the great narrative of History. They explore colonial archives and memories passed down from their grandmother and generations of women in their family. Through video and installation, they aim to create an archive that exists without hegemonic ways of knowledge creation. This archive focuses on the domestic and the everyday: how the act of eating a mango connects one to their ancestry, how something as commonplace as a trivet, or a table napkin, or the table they are on, can carry so much meaning and history built through daily use. The exhibition also served as a place to welcome people in a way that is not always compatible with the contemporary art space. The written component of the thesis centers the idea of welcoming. Wane makes a connection between the importance of hosting in their practice and the feeling of being unwelcome in an institution like the Fine Arts Academy. They write extensively about their decision to show the thesis work outside of the institution, stressing the structures that have made them feel alienated, and elaborating on the tactics they have developed as a result. They also write about the process of making this work, speaking on their relationship with family and their various influences, rooted in intersectional feminism, and how these have inspired the work presented in the exhibition. Among these thoughts, are interspersed a few of the texts presented in the exhibition.
Keywords: memory; archives; institutional critique; kuvataide; perheet; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|